(untitled) (Conference on English Language Teaching, 2025)
The Common European Framework of Reference for Languages (CEFR) has received an increasing currency in Asian countries. It has been adopted as a standard proficiency for several foreign language learning in Indonesia such as German, Arabic, Indonesian for Foreign Speakers (BIPA), and the newly adapted one, English. This study present the theoretical discussion on CEFR, its adoption in Non-European countries and its feasibility for Indonesia’s foreign language learning policy. Data are collected by searching relevant literature namely book and journal articles published by reputable publishers. The data then are analyzed descriptively. The result shows CEFR has been adopted by non-European countries for a long time. Its adoption in the Southeast Asian region results in the increased quality of education. The proximity in the characteristics of CEFR and the Merdeka Curriculum made the framework feasible to be adopted by Indonesia. However, issues such as teachers’ insufficient knowledge of English, their lack of CEFR familiarity, and the absence of a language portfolio and the Reference Level Description need to be addressed accordingly.